A novel approach for electrical tuning of nano-textured zinc oxide surfaces for ultra-sensitive troponin-T detection. Issue 24 (3rd September 2015) - Munje, Rujuta D.; Jacobs, Michael; Muthukumar, Sriram; Quadri, Bilal; Shanmugam, Nandhinee Radha; Prasad, Shalini
Abstract : We have developed a novel and ultrasensitive biosensor by functionalizing surface terminations of zinc oxide using two specific linker chemistries, which has enabled fg mL −1 level detection of a cardiac stress biomarker, troponin-T. Abstract : We have developed a label-free, non-faradaic, electrochemical sensor for ultra-sensitive detection of a cardiac biomarker, troponin-T by utilizing the stoichiometric surface compositions of nanotextured zinc oxide (ZnO) thin films. In this study, we show how the performance of a nanotextured zinc oxide based non-faradaic biosensor is modulated by differences in the fabrication parameters of the metal oxide thin film as well as the choice of cross-linkers. Two cross-linking molecules, dithiobis succinimidyl propionate and 3-aminopropyl triethoxysilane, demonstrate significantly different binding chemistries with zinc oxide. The non-faradaic electrochemical behaviour of the sensor due to the two linkers is compared by analyzing the troponin-T dose response using electrochemical impedance spectroscopy (EIS). The sensor performance associated with both linkers is compared based on the dynamic range and limit of detection. The sensor utilizing zinc surface terminations demonstrated a wider dynamic range between the two linkers. This range extended from 26% to 54% in phosphate buffered saline and from 21% to 65% in human serum, for a concentration range from 10 fg mL −1 to 1 ng mL −1 of troponin-T. The limit of detection was found to be at 10 fg mL −1 and has potential utility in the development of point-of-care (POC) diagnostics for cardiovascular diseases. Fluorescence quantification analysis was also performed to further validate the specificity of the linker binding to the ZnO films. An ultrasensitive troponin-T biosensor can be designed by leveraging the zinc termination based surface chemistry for selective protein immobilization.